Fescue Hay Cost-Return Budget in Central and Eastern Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2012)
This publication provides estimated cost and returns for forward farm planning for fescue hay in central and eastern Kansas.
MF2146_2012_12
Keywords: MF2146; Crops; Economics; MF